High-rigidity transparent rigid polyvinyl chloride granule and preparation method thereof
By adding acrylonitrile-styrene resin and toughening additives to the polyvinyl chloride pellets, combining organic tin heat stabilizer and processing modifiers, a composite toughening system is formed, which solves the problem of insufficient rigidity of the polyvinyl chloride pellets and significantly improves its impact resistance and rigidity.
Patent Information
- Application Number
- CN202411977158.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
Existing modified polyvinyl chloride pellets are prone to warping or deforming when under pressure or vacuum negative pressure, and are insufficient in rigidity, which limits their application range.
By adding acrylonitrile-styrene resin and toughening additives, combined with organic tin heat stabilizer and processing modifier, a composite toughening system is formed to improve the rigidity and impact resistance of polyvinyl chloride pellets.
It significantly improves the rigidity and impact resistance of polyvinyl chloride pellets, and solves the problems of extruded products being easily warped when under pressure and blow-molded products being easily deformed when under vacuum.
Smart Images

Figure BDA0005220704790000091 
Figure BDA0005220704790000092 
Figure BDA0005220704790000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pipe materials, and in particular relates to a high-rigidity transparent hard polyvinyl chloride granular material and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is the third largest synthetic polymer plastic in the world (after polyethylene and polypropylene). Pure polyvinyl chloride resin is a hard thermoplastic substance, its decomposition temperature is very close to the plasticization temperature, and its mechanical strength is poor. Therefore, it is impossible to use polyvinyl chloride resin to mold products. Plasticizers, stabilizers, fillers, etc. must be added to improve the performance to make polyvinyl chloride plastics, and then processed into various products.
[0003] Although polyvinyl chloride has developed into a general-purpose resin with large output, excellent comprehensive performance and wide application, people are also constantly trying to modify it from various aspects (such as processing performance, impact resistance, heat resistance and plasticizer migration, etc.), but its own defects still restrict its further development. Its defects are mainly manifested in excessively high melt viscosity and poor fluidity. The decomposition of polyvinyl chloride is always accompanied during the processing, which damages the processing performance of polyvinyl chloride. After decomposition, unsaturated double bonds are formed on the main chain, resulting in a decrease in polymer performance. Although polyvinyl chloride has good chemical corrosion resistance and flame retardancy, after ordinary modification, the bending strength is only 60MPa and the bending modulus is only about 2000MPa. The rigidity of the product is low, which limits its application range.
[0004] Styrene-acrylonitrile resin, also known as AS resin, is a colorless and transparent thermoplastic resin with high temperature resistance, excellent gloss and chemical resistance, as well as excellent hardness, rigidity, dimensional stability and high rigidity. It is obtained by suspension polymerization of acrylonitrile and styrene as raw materials. It can also be initiated by thermal initiators or by emulsion polymerization. Due to the inherent transparency of the resin, it is used to manufacture transparent plastic products. However, due to the strong intermolecular force, the aggregate is rigid, and the molecular chains can be arranged regularly to form a high degree of crystallization, the impact resistance is reduced, and the cantilever beam notched impact strength is only 3 to 5 kJ / m 2 , it is brittle at room temperature.
[0005] At present, the modification of polyvinyl chloride in China mainly focuses on improving its processing performance, impact resistance, heat resistance and plasticizer migration. Among them, there are several ways to modify the processing performance: adding plasticizers, processing aids, and low melting point lubricants. These ways can effectively reduce the melt viscosity of polyvinyl chloride and improve processing performance, but without exception, they will cause the loss of physical and mechanical properties, especially the bending strength, which drops sharply from 60MPa to 45MPa, seriously affecting the normal use of downstream products.
[0006] The polyvinyl chloride label strips and IC packaging granules currently available on the market have the following defects: they are not resistant to high temperatures and are easily deformed when heated, which is manifested in the relatively low Vicat softening point temperature of the material; they are not resistant to pressure and are easily deformed during installation and use, which is manifested in the relatively low bending strength and bending modulus. Summary of the invention
[0007] In view of the problems in the prior art, the present invention provides a highly rigid transparent rigid polyvinyl chloride pellet, which solves the problems that the existing modified polyvinyl chloride pellet extruded products are easy to warp under pressure, and the blow molded products are easy to deform under vacuum negative pressure. The present invention improves the rigidity of the blended pellets through the high physical and mechanical properties of acrylonitrile-styrene resin, and reduces the impact on the rigidity of the blended pellets while improving the impact resistance by using a composite toughening system of a toughening aid and a processing modifier.
[0008] In order to achieve the above technical objectives, a technical solution of the present invention is:
[0009] High rigidity transparent rigid polyvinyl chloride granules, the quality formula is as follows:
[0010] 100 parts of PVC resin, 20-50 parts of acrylonitrile-styrene resin, 5-8 parts of organic tin heat stabilizer, 0-5 parts of toughening additive, 2-4 parts of lubricant, 20-40 parts of processing modifier, and 1-2 parts of natural paraffin release agent.
[0011] The above technical solution has the following beneficial effects:
[0012] (1) The present invention can improve the rigidity of the blended pellets by utilizing the relatively high physical and mechanical properties of the acrylonitrile-styrene resin, and the composite toughening system of the toughening aid and the processing modifier improves the impact resistance while reducing the influence on the rigidity of the blended pellets.
[0013] (2) The present invention solves the problems of existing modified polyvinyl chloride pellet extrusion products being prone to warping under pressure and blow-molded products being prone to deformation under vacuum and negative pressure.
[0014] Preferably, the mass ratio of acrylonitrile resin to styrene resin in the acrylonitrile-styrene resin is 1:1-1:3, and the melt index of the acrylonitrile-styrene resin is 3.0-5.0 g / 10 min; the modified resin adopts acrylonitrile-styrene resin, and the mass ratio of acrylonitrile resin to styrene resin in the resin is 1:1-1:3, and the resin melt index is 3.0-5.0 g / 10 min; since the melt viscosity of polyvinyl chloride resin is large and difficult to process, in order to solve this problem, adding acrylonitrile-styrene resin can reduce the melt viscosity of polyvinyl chloride resin, and the bending strength of acrylonitrile-styrene resin is about 100 MPa and the bending modulus is about 3500 MPa, so the defect of high melt viscosity and difficulty in processing of polyvinyl chloride can be overcome while improving the overall rigidity of the mixture;
[0015] Preferably, the organic tin heat stabilizer adopts a composite stabilizer of dibutyltin maleate and methyltin mercaptan, and the mass ratio of dibutyltin maleate stabilizer and methyltin mercaptan stabilizer is 1:1 to 1:3; dibutyltin maleate stabilizer is an organic tin compound, and its structure combines maleate and dibutyltin groups. This structure gives dibutyltin maleate good thermal stability and transparency, so that it can effectively prevent yellowing in polyvinyl chloride products, maintain the color and transparency of the material, and as a heat stabilizer, it can inhibit the generation of HCl at the processing temperature of polyvinyl chloride, thereby preventing the chain breaking reaction and delaying the degradation process of polyvinyl chloride. Its high thermal stability means that even in a high temperature environment, it can maintain the mechanical strength and appearance quality of polyvinyl chloride, but the lubrication effect is general; to solve this problem, adding a small amount of mercaptan organic tin stabilizer can make up for this deficiency and form a composite stabilizer system with both heat resistance and thermal stability.
[0016] Preferably, the toughening aid is at least one of methyl methacrylate-butadiene-styrene resin and chlorinated polyethylene resin; methyl methacrylate-butadiene-styrene resin is polymerized by methyl methacrylate, butadiene and styrene by emulsion polymerization, and has a core-shell structure in the submicroscopic morphology. When the blend is impacted, the core composed of the rubber phase causes stress concentration to induce a large number of silver streaks to absorb the impact energy, and the elasticity of butadiene makes the blend more tough, and has a good toughening effect; chlorinated polyethylene resin is used as a toughening agent, and chlorinated polyethylene particles exist in the PVC matrix in an "island" structure. In the fracture process of chlorinated polyethylene particles toughening PVC, chlorinated polyethylene particles as dispersed phases mainly play a stress concentration role, and release static tension stress through chlorinated polyethylene particles to induce a large range of plastic deformation in the matrix to absorb energy. When the material is impacted, the elastomer itself breaks and extends or forms cavities to absorb energy. Holes can cause stress concentration to induce a large number of silver streaks and shear bands, consume a lot of energy, and achieve the purpose of toughening. Chlorinated polyethylene has good compatibility with polyvinyl chloride and good interface bonding performance, and can effectively exert the toughening effect of chlorinated polyethylene.
[0017] Preferably, the lubricant is at least one of glycerol partial fatty acid ester, fatty acid complex ester, polyethylene wax and oxidized polyethylene wax; glycerol partial fatty acid ester and fatty acid complex ester are prepared by reacting fatty acid with different alcohols. In addition to having good lubrication effect, they can also improve the dispersibility and wettability of polyvinyl chloride resin. Fatty acid ester has good compatibility with polyvinyl chloride resin, has balanced internal and external lubrication effects, and has little effect on adhesion performance; in addition, fatty acid ester also has the effect of plasticizer, which can reduce the viscosity of polyvinyl chloride resin and improve the fluidity of polyvinyl chloride resin. Polyethylene wax and oxidized polyethylene wax are a kind of fully saturated ethylene homopolymer. In the process of extrusion or calendering, polyvinyl chloride resin is subjected to shear stress and enters the micropores of the cavity wall of the processing equipment, hindering the flow of the melt and causing wall sticking, which will reduce the processing performance and extrusion appearance smoothness of the product. Polyethylene wax and oxidized polyethylene wax can mostly overflow on the melt surface and form a lubricating film between the interface with the processing machinery, thereby reducing the friction between the polyvinyl chloride resin and the metal surface of the processing equipment.
[0018] Preferably, the processing modifier is a blend of methyl methacrylate-acrylate copolymer and α-methylstyrene, and the mass ratio of methyl methacrylate-acrylate copolymer to α-methylstyrene is 1:1 to 3:1; the main component of methyl methacrylate and acrylate copolymer is methyl methacrylate, and after mixing it with polyvinyl chloride resin, the processing modifier first melts under the action of heat and shear force, and then adheres to the polyvinyl chloride resin to form a network structure, and at the same time transmits the external shear force to the resin to promote the plasticization of polyvinyl chloride, so that the melt shear force is increased, thereby improving the effect of absorbing impact energy of the blend and increasing the notched impact strength of the blend; compared with styrene, one hydrogen atom of α-methylstyrene is replaced by a methyl group, so that it cannot form a high polymer by itself, and can be polymerized in a variety of polymerization processes under heat or with the action of a catalyst to produce low molecular weight polymers or as a monomer for producing resins and plastics. As a processing modifier for polyvinyl chloride, it can significantly reduce or eliminate the shear stress in the processing process, reduce the equilibrium torque, promote plasticization performance, improve fluidity and improve mechanical properties.
[0019] Preferably, the natural paraffin release agent is solid paraffin refined from solid hydrocarbons in petroleum or shale oil; it has the appearance of white solid crystals, low oil content, good plasticity, certain strength and toughness, solid paraffin is incompatible with polyvinyl chloride resin, but has high lubrication efficiency, can improve the lubricity between polymer and metal, improve extrusion efficiency, improve the dispersibility of colorants, and give the product a good gloss.
[0020] In order to achieve the above technical objectives, the present invention also provides a method for preparing the above high-rigidity transparent rigid polyvinyl chloride granules, the steps comprising:
[0021] Prepare PVC resin, acrylonitrile-styrene resin, organotin heat stabilizer, toughening aid, lubricant, processing modifier and natural paraffin release agent according to the formula ratio;
[0022] Adding acrylonitrile-styrene resin into a ball mill for ball milling to form acrylonitrile-styrene resin powder;
[0023] Add PVC resin and organotin heat stabilizer into a high-speed mixer and stir for 5 to 10 minutes to obtain a premixed powder;
[0024] Add lubricant, processing modifier and natural paraffin release agent to the premixed powder, stir evenly, then add acrylonitrile-styrene resin powder and toughening agent, stir until completely mixed, and obtain mixed powder;
[0025] The mixed powder is added into a low-speed mixer and stirred for 10 to 20 minutes, then cooled, and then placed into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain high-rigidity transparent rigid polyvinyl chloride pellets.
[0026] The above preparation method has the following advantages:
[0027] Through a simple and efficient mixing and granulation process, physical modification of polyvinyl chloride / heat-resistant modified resin and toughening agent is achieved, and the rigidity of polyvinyl chloride resin is improved.
[0028] Preferably, the stirring and mixing temperature of the PVC resin and the organic tin heat stabilizer is 110-130°C and the pressure is 0.3-0.7MPa. The temperature of 110-130°C helps other additives to penetrate into the gaps of the polyvinyl chloride resin / heat-resistant modified resin, so that the additives are evenly dispersed in the resin. The temperature above 100°C is also conducive to the evaporation of moisture and various small molecular volatiles in the material.
[0029] Preferably, the stirring and mixing temperature of the low-speed mixer is 40-60°C, the conical twin-screw compression ratio of the twin-screw extruder is 5.0, the screw speed is 30-50r / min, the extrusion granulation temperature is 140-170°C, and the residence time is 1-2min; after low-speed mixing, the mixed powder is completely cooled to prevent material decomposition and additive volatilization caused by untimely heat dissipation. DETAILED DESCRIPTION
[0030] The following describes the embodiments of the present invention in detail, but does not limit the claims of the present invention in any way.
[0031] In order to solve the problems that the existing modified polyvinyl chloride pellet extrusion products are easy to warp under pressure and the blow molded products are easy to deform under vacuum negative pressure, the present invention provides a formula of high rigidity transparent rigid polyvinyl chloride pellets, and the proportions of each component are as follows (by mass):
[0032] 100 parts of PVC resin;
[0033] 20 to 50 parts of acrylonitrile-styrene resin, wherein the mass ratio of acrylonitrile resin to styrene resin in the acrylonitrile-styrene resin is 1:1 to 1:3, preferably 1:3; the melt index of the acrylonitrile-styrene resin is 3.0 to 5.0 g / 10 min, preferably 3.0 g / 10 min;
[0034] 5-8 parts of an organic tin heat stabilizer, which can be a composite stabilizer of dibutyltin maleate stabilizer and methyltin mercaptan stabilizer, and the mass ratio of the dibutyltin maleate stabilizer to the methyltin mercaptan stabilizer is 1:1 to 1:3, preferably 1:3;
[0035] 0-5 parts of toughening agent, which can be at least one of methyl methacrylate-butadiene-styrene resin and chlorinated polyethylene resin;
[0036] 2-4 parts of lubricant, which can be at least one of glycerol partial fatty acid ester, fatty acid complex ester, polyethylene wax and oxidized polyethylene wax;
[0037] 20-40 parts of processing modifier, which can be a blend of methyl methacrylate-acrylate copolymer and α-methylstyrene, the mass ratio of methyl methacrylate-acrylate copolymer to α-methylstyrene is 1:1-3:1, preferably 2:1;
[0038] 1-2 parts of natural paraffin release agent, which can be solid paraffin extracted from solid hydrocarbons in petroleum or shale oil;
[0039] In the above recipe:
[0040] (1) The organic tin heat stabilizer adopts a composite stabilizer of dibutyltin maleate and methyltin mercaptan, and the mass ratio of dibutyltin maleate stabilizer to methyltin mercaptan stabilizer is 1:1 to 1:3; dibutyltin maleate stabilizer is an organic tin compound, and its structure combines maleate and dibutyltin groups. This structure gives dibutyltin maleate good thermal stability and transparency, so that it can effectively prevent yellowing in polyvinyl chloride products and maintain the color and transparency of the material. As a heat stabilizer, it can inhibit the generation of HCl at the processing temperature of polyvinyl chloride, thereby preventing the chain breaking reaction and delaying the degradation process of polyvinyl chloride. Its high thermal stability means that even in high temperature environment, it can maintain the mechanical strength and appearance quality of polyvinyl chloride, but the lubrication effect is general; to solve this problem, adding a small amount of mercaptan organic tin stabilizer can make up for this deficiency and form a composite stabilizer system with both heat resistance and thermal stability;
[0041] (2) Acrylonitrile-styrene resin is used as the modified resin in the formula, and the mass ratio of acrylonitrile resin to styrene resin in the resin is 1:1 to 1:3, and the resin melt index is 3.0 to 5.0 g / 10 min. Since the melt viscosity of polyvinyl chloride resin is high, it is difficult to process. To solve this problem, adding acrylonitrile-styrene resin can reduce the melt viscosity of polyvinyl chloride resin, and the bending strength of acrylonitrile-styrene resin is about 100 MPa and the bending modulus is about 3500 MPa. Therefore, the overall rigidity of the mixture can be improved while overcoming the defect of high melt viscosity of polyvinyl chloride that is difficult to process.
[0042] (3) The toughening agent is at least one of methyl methacrylate-butadiene-styrene resin and chlorinated polyethylene resin; methyl methacrylate-butadiene-styrene resin is polymerized by emulsion polymerization of methyl methacrylate, butadiene and styrene. It has a core-shell structure in the submicroscopic morphology. When the blend is impacted, the core composed of the rubber phase causes stress concentration to induce a large number of silver streaks to absorb the impact energy, and the butadiene in the toughening agent has elasticity to make the blend more tough, which has a good toughening effect; chlorinated polyethylene resin is used as a toughening agent, and chlorinated polyethylene particles exist in the PVC matrix in an "island" structure. In the fracture process of chlorinated polyethylene particles toughening PVC, chlorinated polyethylene particles as dispersed phases mainly play a role in stress concentration, and release static tension stress through chlorinated polyethylene particles to induce a large range of plastic deformation in the matrix to absorb energy. When the material is impacted, the elastomer itself breaks and stretches or forms cavities to absorb energy. Holes can cause stress concentration to induce a large number of silver streaks and shear bands, consume a lot of energy, and achieve the purpose of toughening. Chlorinated polyethylene has good compatibility with polyvinyl chloride and good interface bonding performance, and can effectively exert the toughening effect of chlorinated polyethylene.
[0043] (4) The lubricant is one or two of glycerol partial fatty acid esters, fatty acid complex esters, polyethylene wax and oxidized polyethylene wax; glycerol partial fatty acid esters and fatty acid complex esters are prepared by reacting fatty acids with different alcohols. In addition to having a good lubricating effect, they can also improve the dispersibility and wettability of polyvinyl chloride resin. Fatty acid esters have good compatibility with polyvinyl chloride resin, have balanced internal and external lubrication effects, and have little effect on adhesion performance; in addition, fatty acid esters also have the effect of plasticizers, which can reduce the viscosity of polyvinyl chloride resin and improve the fluidity of polyvinyl chloride resin. Polyethylene wax and oxidized polyethylene wax are a kind of fully saturated ethylene homopolymer. During the processing of extrusion or calendering, polyvinyl chloride resin is subjected to shear stress and enters the micropores of the cavity wall of the processing equipment, hindering the flow of the melt and causing wall sticking, which will reduce the processing performance and extrusion appearance smoothness of the product. Polyethylene wax and oxidized polyethylene wax can mostly overflow on the melt surface and form a lubricating film between the interface with the processing machinery, thereby reducing the friction between the polyvinyl chloride resin and the metal surface of the processing equipment.
[0044] (5) The processing modifier is a blend of methyl methacrylate-acrylate copolymer and α-methylstyrene, and the mass ratio of methyl methacrylate-acrylate copolymer to α-methylstyrene is 1:1 to 3:1; the main component of methyl methacrylate-acrylate copolymer is methyl methacrylate. After mixing it with polyvinyl chloride resin, the processing modifier first melts under the action of heat and shear force, and then adheres to the polyvinyl chloride resin to form a network structure, and at the same time transmits the external shear force to the resin to promote the plasticization of polyvinyl chloride, thereby increasing the melt shear force, thereby improving the blend's effect of absorbing impact energy and increasing the notched impact strength of the blend.
[0045] (6) Natural paraffin release agent is solid paraffin refined from solid hydrocarbons in petroleum or shale oil; it has the appearance of white solid crystals, low oil content, good plasticity, certain strength and toughness. Solid paraffin is incompatible with polyvinyl chloride resin, but has high lubrication efficiency, can improve the lubricity between polymer and metal, improve extrusion efficiency, improve the dispersion of colorants, and give the product a good gloss.
[0046] A preparation method is provided based on the above formulation, the steps comprising:
[0047] Prepare PVC resin, acrylonitrile-styrene resin, organotin heat stabilizer, toughening aid, lubricant, processing modifier and natural paraffin release agent according to the formula ratio;
[0048] Adding acrylonitrile-styrene resin into a ball mill for ball milling to form acrylonitrile-styrene resin powder;
[0049] Adding PVC resin and organotin heat stabilizer into a high-speed mixer and stirring for 5 to 10 minutes to obtain a premixed powder; the stirring and mixing temperature of the PVC resin and the organotin heat stabilizer is 110 to 130° C. and the pressure is 0.3 to 0.7 MPa;
[0050] Add lubricant, processing modifier and natural paraffin release agent to the premixed powder, stir evenly, then add acrylonitrile-styrene resin powder and toughening agent, stir until completely mixed, and obtain mixed powder;
[0051] The mixed powder is added to a low-speed mixer and stirred for 10 to 20 minutes at a stirring and mixing temperature of 40 to 60° C., then cooled, and then placed in a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain high-rigidity transparent hard polyvinyl chloride pellets. The conical twin-screw compression ratio of the twin-screw extruder is 3.0 to 5.0, the screw speed is 30 to 50 r / min, the extrusion granulation temperature is 140 to 170° C., and the residence time is 1 to 2 minutes.
[0052] According to the formula and preparation method of the above-mentioned high-rigidity transparent rigid polyvinyl chloride granules, four kinds of high-rigidity transparent rigid polyvinyl chloride granules are specifically prepared. The proportions (in parts by mass) of the formula components in the six implementation plans (Examples 1 to 6) are shown in Table 1:
[0053] Table 1 Recipe group distribution ratio table (unit: portion)
[0054]
[0055] The properties of the high-rigidity transparent rigid polyvinyl chloride granules prepared by the four implementation schemes in Table 1 and the commercially available common transparent rigid polyvinyl chloride granules were tested, and the test results are compared as shown in Table 2:
[0056] Table 2 Performance test results comparison table
[0057]
[0058]
[0059] In Table 2:
[0060] (1) Flexural strength and flexural modulus test speed 2 mm / min.
[0061] (2) Test conditions for negative pressure test: test pressure -50KPa, negative pressure extraction time 10S, pressure stabilization 10S, test time 5S, quantitative air intake 5S, pressure division time 5S.
[0062] (3) The comparative example uses commercially available ordinary transparent rigid polyvinyl chloride granules.
[0063] In summary, the present invention has the following advantages:
[0064] 1. The present invention can improve the rigidity of the blended pellets through the high physical and mechanical properties of the acrylonitrile-styrene resin, and the composite toughening system of the toughening aid and the processing modifier improves the impact resistance while reducing the influence on the rigidity of the blended pellets.
[0065] 2. The present invention solves the problems of existing modified polyvinyl chloride pellet extrusion products being prone to warping under pressure and blow-molded products being prone to deformation under vacuum and negative pressure.
[0066] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. High rigidity transparent rigid polyvinyl chloride granules, characterized by: Its quality formula is as follows: 100 parts of PVC resin, 20-50 parts of acrylonitrile-styrene resin, 5-8 parts of organic tin heat stabilizer, 0-5 parts of toughening additive, 2-4 parts of lubricant, 20-40 parts of processing modifier, and 1-2 parts of natural paraffin release agent.
2. The high-rigidity transparent rigid polyvinyl chloride granules according to claim 1, characterized in that: The mass ratio of acrylonitrile resin to styrene resin in the acrylonitrile-styrene resin is 1:1 to 1:3, and the melt index of the acrylonitrile-styrene resin is 3.0 to 5.0 g / 10 min.
3. The high-rigidity transparent rigid polyvinyl chloride granules according to claim 1, characterized in that: The organic tin heat stabilizer adopts a composite stabilizer of dibutyltin maleate stabilizer and methyltin mercaptan, and the mass ratio of the dibutyltin maleate stabilizer to the methyltin mercaptan stabilizer is 1:1-1:
3.
4. The high-rigidity transparent rigid polyvinyl chloride granules according to claim 1, characterized in that: The toughening aid is at least one of methyl methacrylate-butadiene-styrene resin and chlorinated polyethylene resin.
5. The high-rigidity transparent rigid polyvinyl chloride granules according to claim 1, characterized in that: The lubricant is at least one of glycerol partial fatty acid ester, fatty acid complex ester, polyethylene wax and oxidized polyethylene wax.
6. The high-rigidity transparent rigid polyvinyl chloride granules according to claim 1, characterized in that: The processing modifier is a blend of methyl methacrylate-acrylate copolymer and alpha-methylstyrene, and the mass ratio of methyl methacrylate-acrylate copolymer to alpha-methylstyrene is 1:1-3:
1.
7. The high-rigidity transparent rigid polyvinyl chloride granules according to claim 1, characterized in that: The natural paraffin wax release agent is solid paraffin wax refined from solid hydrocarbons in petroleum or shale oil.
8. A method for preparing the high-rigidity transparent rigid polyvinyl chloride granules according to any one of claims 1 to 7, comprising the steps of: Prepare PVC resin, acrylonitrile-styrene resin, organotin heat stabilizer, toughening aid, lubricant, processing modifier and natural paraffin release agent according to the formula ratio; Adding acrylonitrile-styrene resin into a ball mill for ball milling to form acrylonitrile-styrene resin powder; Add PVC resin and organotin heat stabilizer into a high-speed mixer and stir for 5 to 10 minutes to obtain a premixed powder; Add lubricant, processing modifier and natural paraffin release agent to the premixed powder, stir evenly, then add acrylonitrile-styrene resin powder and toughening agent, stir until completely mixed, and obtain mixed powder; The mixed powder is added into a low-speed mixer and stirred for 10 to 20 minutes, then cooled, and then placed into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain high-rigidity transparent rigid polyvinyl chloride pellets.
9. The method for preparing high-rigidity transparent rigid polyvinyl chloride granules according to claim 8, characterized in that: The stirring and mixing temperature of the PVC resin and the organic tin heat stabilizer is 110-130° C., and the pressure is 0.3-0.7 MPa.
10. The method for preparing high-rigidity transparent rigid polyvinyl chloride granules according to claim 8, characterized in that: The stirring and mixing temperature of the low-speed mixer is 40-60° C., the conical twin-screw compression ratio of the twin-screw extruder is 3.0-5.0, the screw speed is 30-50 r / min, the extrusion granulation temperature is 140-170° C., and the residence time is 1-2 min.
Citation Information
Cited By
Transparent anti-impact modifier for yellowing-resistant polyvinyl chloride and preparation method of transparent anti-impact modifier
CN119875022A